Are fixed-term jobs bad for your health? A comparison between Western Germany and Spain - Vanessa Gash; Antje Mertens; Laura Romeu Gordo (Fachhochschule für Wirtschaft Berlin, IMB Institute of Management Berlin, 2006)
In this paper we use panel data to analyse the health effects of fixed-term contract status on men and women in western Germany and Spain. This paper asks whether the changes in the employment relationship due to employment law liberalisation have altered the positive health effects associated with employment (Goldsmith et al. 1996; Jahoda 1982). Using contract type information on switching between unemployment and employment we analyse whether transitions to different contracts have different health effects. We find that unemployed workers show positive health effects at job acquisition, and also find the positive effect to be smaller for workers who obtain a fixed-term job. We also establish surprising differences by gender and country, with women less likely to report positive health effects at job acquisition. For western Germany, this was found to be a function of the dual burden of paid and unpaid care within the home.
Keywords: 330